Effects of glyphosate on the morphology and cell cycle of soybean seedlings tolerant and sensitive to the herbicide - Moraes, Isabella Campos; Novais, Hugo Oliveira; Techio, Vânia Helena; Pereira, Welison Andrade (Pesquisa Agropecuaria Brasileira, 2024)
The objective of this work was to evaluate the phytotoxic and cytogenotoxic effects of glyphosate on the direct development of soybean seedlings tolerant and sensitive to this herbicide. Seeds of one cultivar sensitive to and of two tolerant to glyphosate were placed to germinate in contact with distilled water (control) and two herbicide solutions (distilled water + 0.06 or 0.12% glyphosate), at 25°C, for seven days. Seedling responses to glyphosate were evaluated through the germination test, the seedling growth test, and the cell-cycle analysis (mitotic index and rate of abnormalities), carried out on the third, fourth, fifth, and seventh days after sowing. In the germination test under the herbicide treatments, no normal seedlings were observed for the sensitive cultivar, only for the tolerant ones. The herbicide treatments reduced the length of the seedlings and altered their morphology, making the radicle smaller than the hypocotyl. Regarding cytogenotoxic effects, glyphosate had a mitodepressive action on sensitive and tolerant seedlings, while the rate of abnormalities increased only in the sensitive cultivar. Glyphosate negatively affects the development of soybean seedlings at a macroscopic and cellular level, especially in cultivars sensitive to this herbicide.